Roma, Gypsy Travellers, Gens du Voyage: People who Travel? - Janko Spreizer, Alenka (Two Homelands, 2013)
In this turbulent world, different people live highly mobile lives and some seem to be living on the move. On the other hand, there are people known as Gypsies, Travellers, Gens du Voyage or Roma, imag- ined as nomads, although their mobility has been highly controlled or restricted by repressive regimes, nationstates and local communities of Europe throughout history. Following the “mobility turn” or the “new mobilities paradigm” in social studies and based on ethnographic records of travelling Roma who visited Slovenia as “tourists”, I will look at studies of mobilities of Roma. The intention of this paper is first to shed light on the juridical categories of nomad within a certain historical context. Second, within the new mobilities paradigm, and with reference to the immobile platforms that make mobility possible, I will look at the provision of Travellers’ sites that paradoxically make some Travellers less mobile or even sedentarized.